2011
DOI: 10.1007/s11306-011-0306-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of cerebrospinal fluid reveals changes in the central nervous system metabolism in a rat model of multiple sclerosis

Abstract: Experimental Autoimmune Encephalomyelitis (EAE) is the most commonly used animal model for Multiple Sclerosis (MScl). CSF metabolomics in an acute EAE rat model was investigated using targetted LC–MS and GC–MS. Acute EAE in Lewis rats was induced by co-injection of Myelin Basic Protein with Complete Freund’s Adjuvant. CSF samples were collected at two time points: 10 days after inoculation, which was during the onset of the disease, and 14 days after inoculation, which was during the peak of the disease. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 39 publications
5
83
0
1
Order By: Relevance
“…In addition to γ-glutamyl metabolites, WGCNA also identified multiple branched chain amino acids and phenylalanine and lysine metabolites that were altered in MS patients. Metabolomics studies in rodent EAE have demonstrated changes in branched chain amino acid and histidine metabolism (20,21). Previous studies in MS patients have also noted differences in amino acid metabolism (branched-chain amino acid, alanine, arginine) (22,23) or in multiple amino acids (tryptophan, alanine, and isoleucine) in addition to energy metabolites (24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to γ-glutamyl metabolites, WGCNA also identified multiple branched chain amino acids and phenylalanine and lysine metabolites that were altered in MS patients. Metabolomics studies in rodent EAE have demonstrated changes in branched chain amino acid and histidine metabolism (20,21). Previous studies in MS patients have also noted differences in amino acid metabolism (branched-chain amino acid, alanine, arginine) (22,23) or in multiple amino acids (tryptophan, alanine, and isoleucine) in addition to energy metabolites (24).…”
Section: Discussionmentioning
confidence: 99%
“…A similar strategy involving oral formulation of high dose biotin, which serves as a cofactor for essential carboxylase enzymes required for fatty acid synthesis, has recently been demonstrated to provide benefit in patients with not-active progressive multiple sclerosis 39 . Intriguingly, taurine has previously been identified as a dysregulated metabolite in animal models of multiple sclerosis disease, including nonhuman primate models 40 , and its plasma levels can be used to distinguish PLP-induced experimental autoimmune encephalomyelitis (EAE) mice from naive controls 4144 . At a minimum, these findings demonstrate the utility of global metabolomic analyses in the identification of endogenous metabolites that can serve to modulate cellular phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained metabolite profiling showed that around the onset of EAE, arginine, alanine and branched amino acid levels were significantly decreased compared with normal controls. Whereas, at the peak of the disease, glutamine, O-phosphoethanolamine, branchedchain amino acids and putrescine were significantly increased (Noga et al, 2012). LC/MS and GC/MS can separate different metabolites basing on whether these metabolites can be volatile or derivatized.…”
Section: Application Of Metabolomics In Multiple Sclerosismentioning
confidence: 99%